Proposta de critérios para avaliação qualitativa de ementas - Bessa, Vera (2009)
Objectives: This study aimed to develop a proposal of reference criteria for the qualitative evaluation of menus based on national and international recommendations.Methods: There were selected 36 items of detailed menus qualitative assessment (AQE-d method) of Veiros et al. (2007) for establishment of the menu evaluation criteria. According to the importance of several items to the nutritional and sensorial balance of the menu, we have taken into account each of them for the final classification. The score of a menu is obtained by adding the values of the weighting of criteria met. To allow the qualitative classification of menus percentual intervals were defined corresponding to "very good", "good", "acceptable" and "not acceptable".Results: A reference criteria is proposed for each analysis group, on the basis of healthy eating principles, to which menus must answer to be considered a balanced menu.Conclusions: The tool proposed may be applied associated to the method of AQE by Veiros et al and allows standardization in the quality evaluation of menus by various professionals involved on their elaboration.